2020
DOI: 10.1111/asj.13356
|View full text |Cite
|
Sign up to set email alerts
|

The influence of concentrate‐rich diet on daily sleep and lying postures of Japanese black cows

Abstract: Sleep is one of the essential behaviors in mammalian health and welfare (Schmidt, 2014; Siegel, 2005). Schmidt (2014) theorized that sleep functions in energy conservation, a recovery or recuperative process, neural network reorganization, and an immobilization strategy. Even though each proposed theory of sleep function is paradoxical and has its own shortcomings, all proposed functions can shed light on its importance, not only in adaptation but also in animal production and welfare. Deep sleep occurs only w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Greater lying bouts may reflect animal discomfort and may be due to the effect of the acidogenic diets that lead to damage in the lamina of the foot [ 47 ]. Furthermore, Fukasawa et al [ 48 ] reported similar results, describing a tendency to increase lying bouts when implementing high concentrate feeding compared to forage feeding. The higher nutritive value of the diet has been suggested to influence lying time or lying bouts as well, with increasing lying times associated with a greater body condition score [ 6 ].…”
Section: Discussionmentioning
confidence: 80%
“…Greater lying bouts may reflect animal discomfort and may be due to the effect of the acidogenic diets that lead to damage in the lamina of the foot [ 47 ]. Furthermore, Fukasawa et al [ 48 ] reported similar results, describing a tendency to increase lying bouts when implementing high concentrate feeding compared to forage feeding. The higher nutritive value of the diet has been suggested to influence lying time or lying bouts as well, with increasing lying times associated with a greater body condition score [ 6 ].…”
Section: Discussionmentioning
confidence: 80%